2023
DOI: 10.29333/ejgm/13518
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on mental health in the Middle East: A cross-sectional study

Abstract: <b>Objective: </b>This study aimed to shed the light on the relation between the COVID-19 outbreak and mental health, including depression and anxiety in the Middle East.<br /> <b>Methods: </b>This is a survey-based study that was conducted online to evaluate the impact of the COVID-19 pandemic on mental health in the Middle East countries. The survey was uploaded on Google Form platform and was distributed through Facebook and WhatsApp platform.<br /> <b>Results: <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The findings of H1 confirmed that the behavior of customers has a direct and positive impact on workers' psychological risks. The results indicated that many workers feel worried, uncomfortable, stressed, and frustrated with the behavior of customers, and this result agrees with [15][16][17][18][19][20][21][22][23], who stated that COVID-19 creates psychological effects on individuals such as anxiety, fear, stress, loneliness, uncertainty, disruption, and frustration. The findings of H2 confirmed that the behavior of customers has a direct and positive impact on workers' health risks.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings of H1 confirmed that the behavior of customers has a direct and positive impact on workers' psychological risks. The results indicated that many workers feel worried, uncomfortable, stressed, and frustrated with the behavior of customers, and this result agrees with [15][16][17][18][19][20][21][22][23], who stated that COVID-19 creates psychological effects on individuals such as anxiety, fear, stress, loneliness, uncertainty, disruption, and frustration. The findings of H2 confirmed that the behavior of customers has a direct and positive impact on workers' health risks.…”
Section: Discussionsupporting
confidence: 80%
“…[15], found that the outbreak of infectious diseases, such as COVID-19, can lead to mental health concerns and psychological distress. Other studies, including those by [16][17][18][19][20] have found that the COVID-19 pandemic has had a significant impact on the emotional and social well-being of individuals, families, and society as a whole, either directly or indirectly. While contracting the virus is a concern, the primary psychological risks relate to disruptions in daily life, such as reduced contact with loved ones and changes in work.…”
Section: Psychological Risksmentioning
confidence: 99%